2017
DOI: 10.2174/1573406413666170510103030
|View full text |Cite
|
Sign up to set email alerts
|

C-type Lectin Receptor: Old Friend and New Player

Abstract: During the last two decades, C-type lectin receptors (CLRs) have been demonstrated to play key roles in initiating the host immune response against fungal infection. It is well established that CLRs, such as Dectin-1, Dectin-2, Dectin-3 and Mincle recognize the cell wall component from the infected microorganisms by using their carbohydrate recognition domain (CRD). Upon stimulation, CLRs induce multiple signal transduction cascades through their own immunereceptor tyrosine-based activation motifs (ITAMs) or i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…In agreement with prior reports revealing a role for the Card9/Bcl10/Malt1 complex downstream of Dectin-2 (62), we demonstrated that the loss of Card9 or the inhibition of Malt1 hinder the production of IL-1β and IL-23 by DCs stimulated with live eggs (40). This is consistent with the role of Malt1 in the Dectin-2-mediated activation of the NF-κB subunit c-Rel, which is a key player in the induction of Th17 responses (63).…”
Section: Cd209a Drives Inflammation In Synergy With Dectin-2 and Minclesupporting
confidence: 93%
“…In agreement with prior reports revealing a role for the Card9/Bcl10/Malt1 complex downstream of Dectin-2 (62), we demonstrated that the loss of Card9 or the inhibition of Malt1 hinder the production of IL-1β and IL-23 by DCs stimulated with live eggs (40). This is consistent with the role of Malt1 in the Dectin-2-mediated activation of the NF-κB subunit c-Rel, which is a key player in the induction of Th17 responses (63).…”
Section: Cd209a Drives Inflammation In Synergy With Dectin-2 and Minclesupporting
confidence: 93%
“…CLRs dominate fungal perception and immunity, they can activate the Syk-Card9 pathway through immune receptor tyrosine-based activation motifs (ITAMs) or FcRγ(relate to ITAMs), which in turn activates nuclear factor kappa B(NF-kB) signaling and a series of inflammatory reactions. 126 However, there are differences among receptors (Figure 4), dectin-1 (also known as Clec7a) is a CLR that is expressed by many immunological cells. This molecule recognizes β-glucan and then promotes the production of cytokines to induce inflammation, thus controlling Candida infection mainly.…”
Section: Pattern Recognition Receptorsmentioning
confidence: 99%
“…Lines of evidence have shown that immunoreceptor tyrosine-based activation motif (ITAM)-coupled receptors, including C-type lectin receptors (CLRs) and immunoglobulin superfamily receptors play critical roles in activation of innate immunity against various pathogens [12,13,14,15]. Some of the receptor members, such as Dectin-1/2, and Mincle, are known to sense pathogen-derived material with PAMPs and induce activation of innate immunity [16,17,18,19].…”
Section: Adjuvant Activity Of Mamentioning
confidence: 99%